1989
DOI: 10.1128/aem.55.1.109-115.1989
|View full text |Cite
|
Sign up to set email alerts
|

Diversity within Serogroups of Rhizobium leguminosarum biovar viceae in the Palouse Region of Eastern Washington as Indicated by Plasmid Profiles, Intrinsic Antibiotic Resistance, and Topography

Abstract: Serology, plasmid profiles, and intrinsic antibiotic resistance (IAR) were determined for 192 isolates of Rhizobium leguminosarum biovar viceae from nodules of peas (Pisum sativum L.) grown on the south slope and bottomland topographic positions in eastern Washington State. A total of 3 serogroups and 18 plasmid profile groups were identified. Nearly all isolates within each plasmid profile group were specific for one of the three serogroups. Cluster analysis of IAR data showed that individual clusters were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…There appears to be more variability in plasmid DNA content than in genomic DNA sequences as a whole. This is not surprising since Brockman and Bezdicek (1989) documented considerable variation in the plasmid profiles of field isolates of Rh. leguminosarum hv.…”
Section: Rflp Analysismentioning
confidence: 83%
“…There appears to be more variability in plasmid DNA content than in genomic DNA sequences as a whole. This is not surprising since Brockman and Bezdicek (1989) documented considerable variation in the plasmid profiles of field isolates of Rh. leguminosarum hv.…”
Section: Rflp Analysismentioning
confidence: 83%
“…(1998). The strain Rhizobium leguminosarum biovar viciae T83K3 was used as standard for determination of plasmid molecular weight (Brockman and Bezdicek 1989).…”
Section: Methodsmentioning
confidence: 99%
“…Serotyping allows researchers to gain a superficial picture of the diversity within native rhizobial populations at specific sites, to track the occurrence and distribution of antigenically related bacteria across states, countries, and continents, and to study the autecology of these bacteria in soil (4,7,13,15,17,30,33,36,38,40,42,49,53). Studies carried out with Bradyrhizobium japonicum (24,34,35,43,50,51,54) and Rhizobium leguminosarum (8,19,55) have shown that individual serotypes can be composed of nonidentical strains. As a result, concerns have been raised about the limitations of serological approaches to address various rhizobial phenomena of potential agricultural and ecological significance.…”
mentioning
confidence: 99%